Chemical composition with different drying methods and ruminant methane gas production of Palisada perforata - NUR HIDAYAH; CUK TRI NOVIANDI; ANDRIYANI ASTUTI; KUSTANTINAH KUSTANTINAH (Nusantara Bioscience, 2024)
Abstract. Hidayah N, Noviandi CT, Astuti A, Kustantinah. 2024. Chemical composition with different drying methods and ruminant methane gas production of Palisada perforata. Nusantara Bioscience 16: 37-42. Indonesia is a tropical country with a large diversity of seaweed, but a few studies analyzed it as an ingredient or supplement for ruminant feed. Evaluation of the nutrient content and phenolic compound with different drying methods (freeze-drying and shade-drying) and ruminant gas production from Palisada perforata (Bory) K.W.Nam to know about the potential for ruminant feed and methane mitigation were the goals of this investigation. The nutrient content, kinetic, and methane gas production were analyzed descriptively; meanwhile, the phenolic compound was analyzed with T-tests for the differences among treatments, using 4 replications. The result showed that the nutrient content of P. perforata had higher Organic Matter (OM), Crude Protein (CP), and Nitrogen-Free Extract (NFE) with the freeze-drying method (83.47 vs. 52.85%DM, 19.33 vs. 16.05%DM, and 54.16 vs 26.80%DM, respectively) and the mineral content was higher with shade-drying method (16.53 vs 47.15%DM). The shade-drying method decreased almost 50% of the phenolic compound compared to the freeze-drying method. The kinetic gas production of P. perforata had easily degraded, potentially degraded, and total degraded and fermented fractions at 5.88, 24.91, and 30.80 mL/200 mgDM, respectively; the methane gas production in 24 and 48 hours incubation at 1.80 and 3.01 mL/gDM. The study concluded that the freeze-drying method is better than the shade-drying method to dry P. perforata and this species' potential as ruminant feed and methane mitigation.